Avaliação da qualidade de creches: estudo em um município de São Paulo - Figueirêdo, Ivoneide Gomes (2010)
In the last few decades, the great number of inserted children in institutions of infantile education brought a new permeador element of the infantile development: the daily experience in collective environments. Considering the long daily permanence of children in day-care centers one becomes necessary a supervision of the infantile development therefore the years you initiate are crucial to the acquisition of abilities and knowledge. Thus, this study aimed like general objective evaluate and describe the structural and functional conditions of day care centers in the city of Barueri-SP, and like specific objectives: 1) assess and describe the 21 day care centers in the city based on the eight areas proposed by the instrument Child Care Facility Schedule (CCFS), namely: physical environment, health and safety; nutrition and food service, administration, staff-family interaction, staff-children interaction, observable child behaviour, curriculum; and 2) verify differences between the 21 day care centers in each area proposed by CCFS. In this research, was used to qualitative and quantitative methodology with a descriptive and exploratory. The obtained results through the observation of standard operational routine of all day care centers surveyed, with respect to activities periods, type of meal offered, enrollment procedures, criteria for admission, administrative guidance, administrative staff, denote a well defined policy in strategic level. The results allow us to say that statistically all day care centers are at levels commensurate with the quality standards proposed by the instrument CCFS. However, we can see that some items require more attention on the issue of provision of quality care offered in Barueri, namely: 57.1% of centers had "no existing condition" for the group size and 28.6% for the ratio adult / child, both in the Administration area, with indicators that exceded those given by the World Health Organization. In the Health and safety area "objectionable condition" in 38.1% and 23.8% on items related to training in first aid and the requirement for annual physical examinations for employees; in Physical Environment area, 23.8% of centers scored "objectionable condition" referring to insufficient space for the number of children present. The items that deserve attention by the City Department of Education and aimed in this research, are uncommon and of easy solution, and will be subject to devolution to the city lodged by the researcher, as a contribution in the pursuit of improving the quality of services, particularly services related to early childhood education.